Tindak Tutur Ekspresif dan Strategi Bertutur Guru Bahasa Indonsia dalam Pembelajaran Teks Prosedur Siswa Kelas VII - Mutia Aulia Maheni; Ermawati Arief; Syahrul Ramadhan; Emidar Emidar (Paedagogie, 2026)
The purpose of this study is twofold. First, it aims to describe the forms of expressive speech acts used by Indonesian language teachers in the learning process of Grade VII at SMPN 2 Padang. Second, it seeks to identify the speaking strategies employed by the teachers during Indonesian language instruction in the same class. This research adopts a qualitative design with a descriptive method. The findings of the study consist of two main points. First, five forms of expressive speech acts were identified in the Indonesian language learning process for Grade VII at SMPN 2 Padang, namely: (1) expressive acts of apologizing, (2) expressive acts of praising, (3) expressive acts of blaming, (4) expressive acts of criticizing, and (5) expressive acts of thanking. Second, four types of speaking strategies were found to be used by the teachers, including: (1) speaking directly without preamble, (2) speaking directly with positive politeness markers, (3) speaking directly with negative politeness markers, and (4) vague speaking strategies. Based on these findings, it can be concluded that Indonesian language teachers in Grade VII at SMPN 2 Padang employ five forms of expressive speech acts and four speaking strategies during the Indonesian language learning process.